2014
DOI: 10.1016/j.fuproc.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Steam co-gasification of brown seaweed and land-based biomass

Abstract: Alkali and alkaline earth species in biomass have self-catalytic activity on the steam gasification to produce hydrogen-rich gas. In this study, three types of biomasses, i.e., brown seaweed, Japanese cedar, apple branch containing different concentrations of alkali and alkaline earth species, and the mix of both of them were gasified with steam in a fixed-bed reactor under atmospheric pressure. The effects of reaction temperature, steam amount and mixing ratio in co-gasification on gas production yields were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 40 publications
1
41
1
Order By: Relevance
“…A higher S/C ratio increases H2 production because of the water gas reaction (R5 and R7) and steam methanation (R8 and R9). These changes in the hydrogen yield are consistent with the results of experiments in Kaewpanha et al [32] and the thermodynamic analysis carried out Vivanpatarakij and Assabumrungrat [33]. …”
Section: Effect Of S/c Ratiosupporting
confidence: 91%
“…A higher S/C ratio increases H2 production because of the water gas reaction (R5 and R7) and steam methanation (R8 and R9). These changes in the hydrogen yield are consistent with the results of experiments in Kaewpanha et al [32] and the thermodynamic analysis carried out Vivanpatarakij and Assabumrungrat [33]. …”
Section: Effect Of S/c Ratiosupporting
confidence: 91%
“…Pre-treatment of macroalgae with water and acid may be employed to remove Mg, K, Na and Ca salts and other mineral matter by up to 90% [94] which can lead to high char levels, but conversely alkaline species can catalytically aid the steam gasification of macroalgae to H2 at temperatures above 700 °C [95]. Higher syngas yields from steam gasification of macroalgae are possible due to their high content of inorganic elements than land based biomass such as Japanese Cedar and Apple branch, however the latter materials can be co-gasified with seaweed in a biorefinery, leading to enhanced syngas yields [95,96].…”
Section: Gasificationmentioning
confidence: 99%
“…Higher syngas yields from steam gasification of macroalgae are possible due to their high content of inorganic elements than land based biomass such as Japanese Cedar and Apple branch, however the latter materials can be co-gasified with seaweed in a biorefinery, leading to enhanced syngas yields [95,96].…”
Section: Gasificationmentioning
confidence: 99%
“…However, different biomass contains different contents of AAEM. Biomass with high content of AAEM was found to be able to improve the gasification performance when it was co-gasified with coal [32][33][34][35][36][37] or with other biomass containing low concentration of AAEM [38]. It is found that some components of AAEM in the biomass were easily volatilized and resulting in the increase in the reactivity of the coal [36,37].…”
Section: Introductionmentioning
confidence: 98%